The sagebrush anthology literature from the silver age of the Old West - Berkove, Lawrence I. (Mark Twain and his circle series., 2006)
"Sixty-eight selections representing writers who spent their creative years in Nevada from the 1860s to the early twentieth century and have become known as the Sagebrush School. Features Mark Twain, Dan De Quille, Sam Davis, Joe Goodman, and Rollin Daggett, and lesser-known writers Arthur McEwen, Fred Hart, and others"--Provided by publisher.